(untitled) (Journal of Biodiversity Conservation and Bioresource Management, 2023)
Fish in aquaculture face stress, which is a major concern due to its effects on the overall wellbeing of the fish. To modulate the stress responses, researchers are turning to the use nutraceuticals rather than chemical drugs. In a six-week long study, holy basil (Ocimum sanctum) was used to observe its effects on stress in Nile tilapia (Oreochromis niloticus). Stress was induced by adding cortisol with the feed as a supplement. Three different treatments (control, stress, stress- basil), each with two replicates, were used to measure serum cortisol, lysozyme activity, macrophage phagocytosis, spleen somatic index, and condition factor. Basil had no significant effect on any of the parameters when comparing the stress and stress basil treatments. But the result showed significant imperative effect of stress due to cortisol supplement in both stress and stress-basil groups. The results suggest that basil may have potentials to modulate the stress response in Nile tilapia. J. Biodivers. Conserv. Bioresour. Manag. 2022, 8(2): 1-12